IMPLEMENTASI PERATURAN WALIKOTA PEKANBARU NOMOR 24 TAHUN 2013 TENTANG PENYELENGGARAAN REKLMAE - Muhammad Pandu Wiraditama; Nurlaila Meilani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The city of Pekanbaru is currently experiencing a very rapid development, which is oriented to the economic and entrepreneurial sectors. This results in the increasing number of organizers or the installation of billboards in the city of Pekanbaru. With the large number of billboards installed in the city of Pekanbaru, the longer the rules do not follow, which will affect the aesthetic aspects of the city, thus requiring serious attention from the government. The purpose of this study was to determine the factors that influence the Implementation of the Pekanbaru Mayor Regulation No. 24 of 2013 concerning the organization of Advertisements in the City of Pekanbaru. This study uses Ripley and Franklin policy implementation concepts based on 3 perspectives, that is : Bureaucracy Compliance Level, Smooth routine and no problems, and performance. This study uses qualitative methods with descriptive data assessment. Data collection techniques through interviews, observation, literature study and documentation by using purposive sampling method in selecting informants. The result of the research is the lack of cooperation between the implementing party and the entrepreneurs who set up the billboard. This can be seen by the number of billboards that have not been in accordance with the rules and lack of supervision from the implementor which causes the problem in the implementation of the billboard has not been implemented optimally. Besides that there is still a lack of facilities and infrastructure as well as Pekanbaru City Satpoll PP experts in disciplining. So that it is necessary to strengthen facilities and infrastructure and train experts by Satpoll PP and also the need for awareness from the public or advertisement entrepreneurs to comply with fennel rules so that the optimal advertisement arrangement is realized in Pekanbaru City.Keywords : Implementation, Public Policy, billboards